Therapist-supported online cognitive therapy for post-traumatic stress disorder (PTSD) in young people: protocol for an early-stage, parallel-group, randomised controlled study (OPTYC trial). Issue 3 (21st March 2022) - Smith, Patrick; Ehlers, Anke; Carr, Ewan; Clark, David; Dalgleish, Tim; Forbes, Gordon; Goldsmith, Kimberley; Griffiths, Helena; Gupta, Monica; King, Dorothy; Miles, Sarah; Plant, Dominic; et al.
Abstract : Introduction: Post-traumatic stress disorder (PTSD) is a disabling psychiatric condition that affects a significant minority of young people exposed to traumatic events. Effective face-to-face psychological treatments for PTSD exist. However, most young people with PTSD do not receive evidence-based treatment. Remotely delivered digital interventions have potential to significantly improve treatment accessibility. Digital interventions have been successfully employed for young people with depression and anxiety, and for adults with PTSD. However, digital interventions to treat PTSD in young people have not been evaluated. The Online PTSD Treatment for Young People & Carers (OPTYC) trial will evaluate the feasibility, acceptability and initial indications of clinical efficacy of a novel internet-delivered Cognitive Therapy for treatment of PTSD in young people (iCT-PTSD-YP). Methods and analysis: This protocol describes a two-arm, parallel-groups, single-blind (outcome assessor), early-stage randomised controlled trial, comparing iCT-PTSD-YP with a waiting list (WL) comparator. N=34 adolescents (12–17 years old), whose primary problem is PTSD after exposure to a single traumatic event, will be recruited from 14 NHS Child and Adolescent Mental Health Services in London and southeast England, from secondary schools and primary care in the same region, or via self-referral from anywhere in the UK using the study website. Individual patient-level randomisation will allocate participants in a 1:1 ratio, randomised using minimisation according to sex and baseline symptom severity. The primary study outcomes are data on feasibility and acceptability, including recruitment, adherence, retention and adverse events (AEs). The primary clinical outcome is PTSD diagnosis 16 weeks post-randomisation. Secondary clinical outcomes include continuous measures of PTSD, anxiety and depression symptoms. Regression analyses will provide preliminary estimates of the effect of iCT-PTSD-YP on PTSD diagnosis, symptoms of PTSD, anxiety and depression relative to WL. Process-outcome evaluation will consider which mechanisms mediate recovery. Qualitative interviews with young people, families and therapists will evaluate acceptability. Ethics and dissemination: The study was approved by a UK Health Research Authority Research Ethics Committee (19/LO/1354). For participants aged under 16, informed consent will be provided by carers and the young person will be asked for their assent; participants aged 16 years or older can provide informed consent without their parent or caregiver's involvement. Findings will be disseminated broadly to participants, healthcare professionals, the public and other relevant groups. Study findings will be published in peer-reviewed journals. Trial registration number: ISRCTN16876240 .